Correction of iron deficiency anemia in patients with gynecological diseases using liposomal iron - T A Fedorova; O M Borzykina; E M Bakuridze; T Yu Ivanets; E V Strelnikova; S G Tsakhilova (IP Berlin A.V., 2017)
Iron deficiency anemia (IDA) - one of the most common conditions in patients with gynecological diseases. Purpose - to evaluate the clinical efficacy and tolerability iron supplements Sideral forte in the treatment of IDA in patients with gynecological. Materials and methods. The study group consisted of 30 women aged 28 to 50 years with uterine myoma, adenomyosis and menorrhagia with iron deficiency anemia. Diagnosis is based on the results of clinical, laboratory and special methods of investigation. All patients revealed a moderate degree of IDA (WHO classification for non-pregnant women). IDA treatment was carried out drug Sideral forte 1 capsule per day for 6 weeks. Dynamic analysis of hematological and ferrokinetic indicators showed increase in the number of red blood cells, hematocrit, hemoglobin level of 104.5±8.5 to 118.2±8.6 g/l in 75% of patients. The level of serum iron in the dynamics of treatment increased from 5.45±2,3 to 11.63±5.82 mmol/l, to the sixth week of treatment and observation. In the dynamics of therapy showed an increase in the levels of ferritin in the group average from 8.0±4.3 to 12.13±4.7 g/l. The increase in Sideral forte dose to 2 capsules per day was needed in 25% of women due to continuing chronic blood loss. Adverse eventswere in 6.7% of patients in the third week of treatment. Allergic reactions were none of the patients. Conclusion. The liposomal iron can be used as antianemic drug in the complex treatment of mild iron deficiency anemia in patients with uterine myoma, adenomyosis and menorrhagia. The frequency of adverse eventswas 6.7%. Allergic reactions were not. Sideral forte was effective in 75% of patients; 25% of patients were needed to solve the issue about the surgical management of the underlying disease, that resulted in chronic blood loss.